Murder of a Medici princess - Murphy, Caroline, 1969- (Oxford University Press, 2008)
Prologue. Part I: A Medici Childhood. 1. The New Medici. 2. "I have never seen a more beautiful baby girl". 3. Growing Up Medici. 4. The Medici as Teenage Girls. Part II: A Medici Princess Grows Up. 1. A Bridegroom for Isabella. 2. Medici Weddings. 3. Zibellini and a Hat Full of Musk. 4. The Duke and Duchess of Bracciano. 5. My Brother and I. 6. Overcome By Sorrow. Part III: The First Lady of Florence. 1. After Eleanora. 2. At Home With Paolo and Isabella. 3. Debt. 4. Conflict. 5. The Baroncelli. 6. The Theatre of Isabella. 1. Fidelities. 2. Troilo. 3. A 'Clandestine' Affair. Part IV.